Wariantywność słowotwórcza w tekście na tle epoki (na przykładzie "Reguły zakonu świętej Klary") = Word-formative variance of a text in the context of the period (on the basis of the example of the "Rule of St. Clare") - Janowska, Aleksandra; Kleszczowa, Krystyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article constitutes a proposition related to a description of the linguistic monuments in the context of conservativity or progressivity of the word-formative doublets which are used in them, and thus to study the nature of the text: its progressivity or regressivity against the background of the period in which the text arose. We may discuss this nature owing to, on the one hand, a comparison with the language of the previous period and on the other hand, a comparison with the contemporary state of affairs.
Keywords: wariancja słowotwórcza; rozwój języka; słowotwórstwo historyczne; word-formative variance; the development of a language; historical word formation